Factors influencing Malaysians’ intention to participate in e-waste recycling - Ahmad, Izzah Az Zahra; Elgharbawy, Amal A.M.; Azam, Md Siddique; Ahmad, Anis Najiha; Abd Aziz, Anis Farihah; Samsudin, Nurhusna; Wan Sulaiman, Wan Syibrah Hanisah; Nordin, Noor Faizul Hadry (UiTM Press, 2025)
The rapid increase in mobile e-waste generation in Malaysia is seen to present significant environmental and health challenges. The factors influencing Malaysians’ intentions to engage in mobile e-waste recycling are explored through the lens of the Theory of Planned Behaviour (TPB). The impact of attitudes, subjective norms, perceived behavioural control, environmental concern, perceived convenience, social media use, and knowledge about e-waste recycling on recycling intentions is examined. Data were collected from a survey of 552 Malaysian mobile e-waste users and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that attitudes, subjective norms, perceived behavioural control, and environmental concern have a significant impact on e-waste recycling intentions. Perceived convenience, knowledge, and social media about e-waste recycling use do not significantly affect recycling intentions. The study extends the TPB model by integrating additional factors and offers empirical evidence on their influence on e-waste recycling behaviour. Policymakers and organisations can use these findings to design targeted interventions that encourage responsible e-waste disposal practices. Future research should examine how demographic factors moderate these effects and explore the role of other psychological constructs in shaping recycling behaviour.